RFID-based seamless multimedia services for smart homes. (18th November 2009) - Ma, Yi-Wei; Lai, Chin-Feng; Hu, Chia-Cheng; Chen, Ming-Chiao; , Yueh-Min Huang
As networks and technology progress, the concept of smart homes has become the main focus of major Computer, Communication and Consumer (3C) companies in recent years. To position specific mobile targets and to integrate all 3C devices in a home are the current main challenges in providing seamless multimedia services for smart homes. For these reasons, this study proposed an intelligent home network system by integrating Radio Frequency Identification (RFID) with Open Service Gateway Initiative (OSGi) to provide a seamless video access system and household safety monitoring system.